(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Nearly half of all deaths in children under-five are attributable to malnutrition, translating into the loss of about 3 million young lives a year. The interaction between malnutrition and infection can create a potentially lethal cycle of worsening illness and deteriorating nutritional status. They have altered defense mechanisms during an early infections process, with an increased synthesis of some acute phase proteins including CRP. Objectives: Objective of the study was to identify whether CRP response is helpful in early detection of infection in severe SAM. It may also help to reduce childhood mortality associated with SAM. Methods: This cross-sectional study was conducted with total 50 SAM patients who were admitted in the Gastroenterology Hepatology and Nutrition unit of Dhaka Shishu (Children) Hospital from October 2010 to March 2011. Immediately after admission, clinical evaluation and management was started after sending several investigations along with serum CRP. Re-evaluation of serum CRP was done approximately after 7 days. Data were analyzed by using SPSS version 24. Results: Among the 50 SAM patients, 29 patients were presented with oedema(group-A) and 21 patients were without oedema (group-B). Majority (40) were below 2 years of age with male predominance. Thirty-five patients were partially immunized [69% in group-A and 71.4% in group-B]. During initial assessment, 46% children were hypothermic and76% were hypoglycemic. Nutritional status (z score) weight-for-age, height/length-for-age, weight for height/length in group-A were -4.56±1.00, -4.27±1.97, -2.71±0.97 and in group- B were -4.65±0.78, -5.06±2.34, -2.58±1.00 respectively. Pneumonia (42%) and diarrhoea (36%) were more common. Increased WBC count was found in 80% patients; and only 10% had low hemoglobin level (<5 gm/dl). Majority (44%) of them had pulmonary infection which was found in their chest X-rays. Immediately after admission serum CRP were high [mean CRP 39.44(±16.04)] in all most all patients, irrespective of their types of malnutrition. After 7 days of management, their CRP became normal [07.24 (± 2.75)], p=<0.001. Mean CRP was less [34.90 (±16.60)] in group-A than in group-B [45.72 (±13.16)] on admission and the finding was statistically significant, p=<0.001. Conclusion: Plasma level of CRP constitute a good screening test for the presence of infection in malnourished children and act as a sensitive indicator of recovery from infection and malnutrition. DS (Child) H J 2020; 36(2): 125-133